Persepsi Guru Terhadap Perlindungan Hukum dalam Proses Belajar Mengajar di Sekolah - Florentina Nining Hastiani (Program Studi Pendidikan Profesi Guru, Universitas Sarjanawiyata Tamansiswa Yogyakarta, Indonesia., 2022)
School as a place for transforming knowledge and also for learning to behave in accordance with norms, where teachers or educators are intermediaries. They have huge responsibilities, because student spend most of their learning time at school. Meanwhile, on average, one teacher has to deal with approximately 20-30 students with a variety of characters at the same time. The aim of this study is to find out the teachers' perceptions of the legal protection they acquire during the teaching and learning process. The research applies descriptive quantitative method with 135 teachers as research subject. The criteria are active teacher at the kindergarten to high school level in Indonesia. The results of the analysis of this study indicate that there are 73 people or 54% of the total respondents show positive perception, and 62 people or 46% are negative perception of legal protection during teaching and learning process. This means that the proportion of teachers with negative perceptions are nearly half of the total respondents. This analysis signifies that there are anxiety regarding to teacher's legal protection during disciplining students. School-related parties should pay attention to this issue while maintaining a balance between the teacher's role in educating with a way of educating that considers children's rights and law